Methods of Technical Improvement of the Football Player - Muminov Feruz Ilxomovich; Fatullaeva Muazzam Azimovna (Research Parks Publishing LLC, 2022)
At the heart of the football game is the struggle of two teams that unite players in a common goal, the pursuit of victory teaches players to act as a team, to help each other, methods of cultivating feelings of friendship and camaraderie are highlighted.